Comparative Analysis of Yeast Replicative Lifespan in Different Trapping Structures Using an Integrated Microfluidic System. Issue 12 (9th November 2020) - Gao, Ziqing; Xu, Jian; Chen, Kaiyue; Wang, Shujing; Ouyang, Qi; Luo, Chunxiong
Abstract: Saccharomyces cerevisiae is an important model to study the molecular mechanisms of eukaryotic cell aging. In previous studies, the replicative lifespan (RLS) of yeast is analyzed mainly by manual microdissection. Microfluidic technologies have gradually replaced this labor‐intensive operation. Many microfluidic devices can trap a single yeast cell and track its entire lifespan. However, a direct comparison between microfluidic device designs and the corresponding evaluated RLS values is limited by the different experimental conditions. This study establishes a microfluidic platform for a systematic comparison among different cell trapping structures. The platform integrates four representative structures (micropads, microchannels, three‐bar jails, and two‐bar cups) and allows simultaneous control with a uniform external condition. The experimentally evaluated RLS values are affected by specific chip structures. Exploration of the underlying mechanism revealed that external mechanical stress caused by the chip structure is the key factor in reducing RLS. The findings indicate that external mechanical stress should be a major reference factor in the selection of microfluidic devices. The study also highlights the importance of further research on the relationship between mechanical stress and aging. Abstract : A microfluidic platform is established for a systematic comparison among different yeast cell trapping structures in replicative lifespan (RLS) assay. The platform integrates four representative structures (micropads, microchannels, three‐bar jails, and two‐bar cups). The experimentally evaluated RLS values are affected by specific chip structures. Exploration of the underlying mechanism reveals that external mechanical stress may be the key factor.